Mechanical characterisation of pentagonal gold nanowires in three different test configurations: A comparative study. (September 2019) - Antsov, Mikk; Polyakov, Boris; Zadin, Vahur; Mets, Magnus; Oras, Sven; Vahtrus, Mikk; Lõhmus, Rünno; Dorogin, Leonid; Vlassov, Sergei
Graphical abstract: Highlights: Mechanical characterization of pentagonal Au nanowires in different configuration. Novel three-point bending configuration providing pure bending conditions. FEM analysis of stress distribution inside nanowires during bending. Comparison of FEM simulation results with results obtained by EBT analytical equations. Ultimate strength of pentagonal Au nanowires. Abstract: Mechanical characterisation of individual nanostructures is a challenging task and can greatly benefit from the utilisation of several alternative approaches to increase the reliability of results. In the present work, we have measured and compared the elastic modulus of five-fold twinned gold nanowires (NWs) with atomic force microscopy (AFM) indentation in three different test configurations: three-point bending with fixed ends, three-point bending with free ends and cantilevered-beam bending. The free-ends condition was realized by introducing a novel approach where the NW is placed diagonally inside an inverted pyramid chemically etched in a silicon wafer. In addition, all three configurations were simulated with a finite element method to obtain better insight into stress distribution inside NWs during bending depending on test conditions. The free-ends configuration yielded elastic modulus similar to a classical fixed-ends approach (88 ± 20 GPa vs 87 ± 16 GPa), indicating the reliability of the proposed method. At the same time, the free-ends configuration benefits from a more favourable NW position relative to the probe with facet facing upwards in contrast to the sharp edge in the case of fixed ends. From the other hand, the free-ends configuration was less suitable for strength measurements, as NW can run into the bottom of the inverted pyramid because of a higher degree of deformation before fracture. The cantilevered-beam configuration was less suitable for mechanical testing with indentation because of the instabilities of the free end under the AFM probe.